Concentration of trace elements in long-finned pilot whales stranded in northern Patagonia, Chile. (February 2020) - Garcia-Cegarra, Ana M.; de A. Padilha, Janeide; Braz, Bernardo Ferreira; Ricciardi, Rocío; Espejo, Winfred; Chiang, Gustavo; Bahamonde, Paulina
Abstract: The use of trace metals and rare-earth elements (REEs) is increasing in the mining, metallurgic, electronic, and automobile industries due to their magnetic, heat-resistant, and phosphorescent properties. While large amounts of these metals are released to the environment, the toxic consequences in marine organisms are poorly understood. In Chile a mass stranding event of long-finned pilot whales (LFPW) ( Globicephala melas ) occurred in 2016 due to unknown consequences. Al, Ce, Cr, Cu, Tl, and Zn concentrations were analyzed in LFPW blubber tissue and correlated with body size and age class of individuals. While Al and Zn were higher in juvenile individuals, Ce, Cu, Cr, and Tl were higher in adults. This study provides the first base line of trace metals and REE in LFPW from the southern hemisphere and demonstrates the existence and persistence of trace elements in marine top predators from remote ecosystems like the Chilean Patagonia. Highlights: A mass stranding of long-finned pilot whales was recorded in 2016 in the Chilean Patagonia. Higher concentrations of Al, Ce, and Zn while lower of Cr, Cu, and Tl were found in long-finned pilot whale blubber tissue. Juveniles had higher concentration of Al and Zn and lower of Ce, Cr, Cu, and Tl than adults. First report of trace elements in long-finned pilot whales inhabiting northern Chilean Patagonia.